Pelatihan Permainan “Potret Diri” Melalui Layanan Informasi di SMA Negeri 1 Palangka Raya - Suriatie, Mimi; Pangestie, Esty Pan; Sangalang, Oktamia Karuniaty; Sukarningsi , Susi (Jurnal Pengabdian Kampus, 2025)
Teachers are expected to be useful for the effectiveness and efficiency of Guidance and Counseling services in schools. Teachers can also act as mentors for their students. To help the educational process and the quality of human resources, one of the government policies is to promote guidance and counseling in schools. The purpose of this community service is to want to know the participation of teachers in implementing the use of the self-portrait game through information services at SMA Negeri 1 Palangka Raya, a sample of 81 teachers at the school. The main data collection tool used the Check List technique, namely: a way to obtain data by creating a list of questions addressed to all teachers at SMA Negeri 1 Palangka Raya. How to analyze the data to test the reality of teacher participation in the school towards the implementation of group guidance services, the community service used percentage calculations. The results of this community service show that almost all components of the objectives in the community service are implemented with a fairly high percentage of 100% by teachers at the school. This means that teachers strongly participate and support Information Services at SMA Negeri 1 Palangka Raya.